TRAIL-R3-related apoptosis: Epigenetic and expression analyses in women with ovarian neoplasia - Braga, Leticia da Conceicao [UNESP]; Alvares da Silva Ramos, Ana Paula; Traiman, Paulo [UNESP]; Silva, Luciana Maria; da Silva-Filho, Agnaldo Lopes [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
Objective. To assess the expression of TRAIL-R3 and the methylation of a CpG island within the TRAIL-R3 promoter both in cystadenoma tumors and primary and metastatic epithelial ovarian carcinoma (EOC).Methods. RNA was obtained from women with normal ovarian (NO) tissues (n = 18), ovarian serous cystadenoma tumors (n = 11) and EOC (n = 16) using Trizol (R). Quantitative PCR (gRT-PCR) was performed to quantify the relative levels of TRAIL-R3. The methylation frequency of the CpG island in the TRAIL-R3 promoter was assessed using the methylation-specific PCR (MSP) assay after DNA bisulfite conversion. The differences between the groups were evaluated using the chi-square, Student's t, ANOVA, Mann-Whitney U, Wilcoxon or Kruskal-Wallis tests as indicated. The survival rates were calculated using the Kaplan-Meier method.Results. Cystadenoma and metastatic EOC tumors expressed significantly more TRAIL-R3 mRNA than primary EOC tumors. Methylation of the TRAIL-R3 promoter was absent in NO tissues, while hemimethylation of the TRAIL-R3 promoter was frequently found in the neoplasia samples with 45.4% of the cystadenoma tumors, 8.3% of the primary EOC samples and 11.1% of the metastatic EOC samples showing at least partial methylation (p = 0.018). Neither the expression of TRAIL-R3 nor alterations in the methylation profile were associated to cumulative progression-free survival or the overall survival in EOC patients.Conclusions. Primary EOC is associated to a lower TRAIL-R3 expression, which leads to a better understanding of the complex disease and highlighting potential therapeutic targets. Promoter DNA methylation was not related to this finding, suggesting the presence of other mechanisms to transcriptional control. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Decoy receptor; TRAIL-R3; Gene expression; Methylation; Ovarian cancer